A view of computers in primary and secondary education - Carale, Monica Isabel Reyes (College of Engineering, 1986)
The manner by which computers are being taught and utilized in the primary and secondary educational system was addressed by this paper. Data was gathered by interviewing school administrators and teachers concerning the development of computers in these schools. Officers and researchers from the Ministry of Education, Culture and Sports (MECS) and the U.P. Institute of Science and Mathematics Education (UP NISMED) were interviewed to investigate the role that the government plays in promoting computer literacy in these levels. The results indicate that less than half of the schools surveyed have computers, and that their use in the classroom is mostly limited to being an object of learning. No official curriculum is specified by the MECS, although schools are encouraged to offer these courses. Teachers and parents were found to approve the introduction of computers at this young age. Some improvements in the students' academic performance and attitude to learning were noted by the teachers. Proposals are also presented that would encourage the introduction of computers in all Filipino schools, especially the public school system.